Paradigm shifters: tricksters and cultural science - Hartley John (Cultural Science)
This paper seeks to link anthropological and economic treatments of the process of innovation and change, not only within a given ‘complex system’ (e.g. a cosmology; an industry) but also between systems (e.g. cultural and economic systems; but also divine and human systems). The role of the ‘Go-Between’ is considered, both in the anthropological figure of the Trickster (Hyde 1998) and in the Schumpeterian entrepreneur. Both figures parlay appetite (economic wants) into meaning (cultural signs). Both practice a form of creativity based on deception, ‘creative destruction’; renewal by disruption and needs-must adaptation. The disciplinary purpose of the paper is to try to bridge two otherwise disconnected domains – cultural studies and evolutionary economics – by showing that the traditional methods of the humanities (e.g. anthropological, textual and historical analysis) have explanatory force in the context of economic actions and complex-system evolutionary dynamics. The objective is to understand creative innovation as a general cultural attribute rather than one restricted only to accredited experts such as artists; thus to theorise creativity as a form of emergence for dynamic adaptive systems. In this context, change is led by ‘paradigm shifters’ – tricksters and entrepreneurs who create new meanings out of the clash of difference, including the clash of mutually untranslatable communication systems (language, media, culture).